The role of mediator suppressor of cytokine signaling (SOCS), toll-like receptor 3 (TLR-3) and nuclear factor kappa B (NFκB) on cytokine production during dengue virus infection - Sri Masyeni; Kuntaman Kuntaman; Aryati Aryati; Muchlis AU. Sofro; Usman Hadi; Gondo Mastutik; Windu Purnomo; Agus Santosa; Muhammad Iqhrammullah; Benediktus Yohan; R. Tedjo Sasmono; Erni J. Nelwan (Narra Sains Indonesia, 2023)
Inability to understand the pathogenesis of severe dengue, in particular the control mechanism of immune responses, has led to high mortality rate for patients with dengue shock syndrome (DSS). The aim of this study was to determine the control mechanism of cytokine production by mediator suppressor of cytokine signaling (SOCS), toll-like receptor 3 (TLR-3) and nuclear factor kappa B (NFκB) during DENV infection. Peripheral blood mononuclear blood cells (PBMC), isolated from healthy individuals, were infected with dengue virus (DENV)-2 strain SJN-006 Cosmopolitan genotype (isolated from Bali, Indonesia). The relative gene expression of SOCS-3, TLR-3, NFκB, and the cytokine genes (interleukin (IL)-6, IL-8, interferon inducible protein 10 (IP-10), and macrophage inflammatory protein-1 beta (MIP-1β)) were measured using qRT-PCR at 6, 12 and 24 hours post infection (hpi). Student t-test and Mann-Whitney test were used to compare the gene expressions while causal correlations were analyzed using regression test and path analyses. DENV-2 infection increased the gene expression of SOCS-3, TLR-3, and NFκB after 12 and 24 hpi. The expression of IL-6, IL-8, IP-10, and MIP-1β genes was increased and peaked at different times post-infection. NFκB and SOCS-3 genes likely have role in the upregulation of IL-8 and IL-6 gene expression, respectively. MIP-1β gene expression was significantly induced by both NFκB and SOCS-3. In conclusion, our study suggested that SOCS-3, TLR-3, and NFκB are important in regulating the production of IL-6, IL-8, IP-10, MIP-1β during early phase of DENV-2 infection. This enriches our understanding on pathogenesis pathway of DENV-associated cytokine storm.